Bridging SROI and Marketing Theory in CSR Evaluation: Beneficiary Perceived Social Return as a Psychometric Construct among Indonesian CSR Beneficiaries - Erna Listiana; Herlan Herlan; Martoyo (Yayasan Sinergi Kawula Muda, 2026)
Measuring CSR impact faces two intertwined limitations. Social Return on Investment (SROI) takes an external vantage point and cannot capture what beneficiaries actually experience, while value and satisfaction frameworks from marketing research remain unintegrated into CSR evaluation. Related constructs such as perceived impact and psychological empowerment touch on beneficiaries' psychological responses but neither bridges SROI's accountability logic with marketing's value-satisfaction mechanisms, nor yields psychometric instruments suited to causal modeling. This study develops Beneficiary Perceived Social Return (BPSR), a new psychometric construct that, to the authors' knowledge, first integrates SROI's social-return logic with marketing's value-satisfaction framework by operationalizing beneficiaries' perceived transformation across four dimensions: Behavioral Self-Regulation Return, Applied Competence Return, Prosocial Awareness Return, and Community Engagement Return. A four-variable causal model spanning CSR Implementation (CSRI), BPSR, Beneficiary Perceived Value (BPV), and Beneficiary Satisfaction (BSAT) was tested via PLS-SEM on 305 beneficiaries of the PLN Peduli CSR program in West Kalimantan, Indonesia. All ten hypotheses were supported. BPSR showed strong psychometric performance (AVE = 0.751; CR = 0.923) and discriminant validity against every other construct. CSRI was the strongest predictor of BPSR, which significantly mediated CSRI's effect on BPV and BSAT alike. Findings show beneficiaries' perceived self-transformation is an indispensable mechanism linking CSR quality to value and satisfaction within Indonesia's state-owned enterprise context. Practically, the study yields a perception-based diagnostic instrument CSR managers can deploy directly, without the cost or complexity of full SROI implementation.